Research progress on remediation of total petroleum hydrocarbons in soil by chemical oxidation - a review - Dai, Yaxing; Liu, Zhihao (Frontiers in Environmental Engineering, 2025)
Chemical oxidation remediation is a technique that involves the addition of chemical oxidants to contaminated soil to degrade total petroleum hydrocarbons (TPHs), with the goal of reducing soil organic matter content or eliminating organic contamination. This paper reviews the research progress of several major chemical oxidation remediation technologies, including hydrogen peroxide (H2O2)-based Fenton and Fenton-like systems, calcium peroxide (CaO2)-based Fenton and Fenton-like systems, and persulfate-activated oxidation systems (e.g., Na2S2O8). Among these, the persulfate-activated oxidation system has recently emerged as a research hotspot due to its potential in eliminating TPHs from soil. The efficiency of TPHs degradation depends significantly on the activation method employed and the oxidative capacity of the system. Consequently, future research should focus on two critical directions: (1) the development of highly efficient, cost-effective, and environmentally sustainable activation methods; and (2) the enhancement of oxidative performance in existing systems, such as Na2S2O8/CaO2 and Na2S2O8/H2O2. In discussing the advancements in these major chemical oxidation remediation technologies, this paper specifically examines various persulfate activation methods and their corresponding treatment efficiencies. The aim is to provide insights and references for the development of efficient, cost-effective, and environmentally friendly persulfate-activated oxidation systems, thereby promoting the application of chemical oxidation remediation technologies in the treatment of petroleum hydrocarbon-contaminated soils.